Audit of outcomes following a community‐based early intensive behaviour intervention program for children with autism in Australia. (28th December 2017) - Wood, Sarah; Christian, Mary P.; Sampson, Amanda
Abstract: Objective: Research studies have shown that early intensive behaviour intervention is an effective treatment for children with autism spectrum disorder (ASD). However a research‐to‐practice gap exists, whereby the interventions effective in university‐based studies are not implemented effectively in community settings. The current study is an audit of outcomes achieved by children with ASD who have completed a community‐based early intensive behaviour intervention program in Australia. Method: The educational placement of 45 participants, following an average 20 hr of intervention per week for 24 months is reported. Standardised assessment results at entry and exit from intervention are reported for a subset of 32 participants. Results: On average the 32 participants demonstrated statistically significant increases in receptive and expressive language, cognitive, and adaptive behaviour skills. Three outcome groups emerged; a 'substantial gain' group (45%), 'moderate gain' group (27.5%), and a 'minimal gain' group (27.5%). Conclusions: The results demonstrate that by implementing 'best practice' early intensive behaviour intervention in a not‐for‐profit, community‐based setting, children with ASD can achieve outcomes comparable to those reported in university‐based research.